Tingkat Pemberian Empulur Sagu yang Difermentasi dengan Kapang Aspergillus niger Terhadap Persentase Karkas Itik Serati Umur 8 Minggu - Achmad Jaelani; Muhammad Irwan Zakir; Kusyanti Kusyanti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
The experiment was aimed to know the level of fermented sago by using Aspergillus niger to dressed carcass percentage of Serati duck 8 weeks age. This experiment was used Completely Randomized Design with 5 treatments and 4 replicates (control, 10% 20%, 30% and 40% of fermented sago). Data was analyzed by using analysis of variance and followed by Duncann Multirange test. The Optimal use of fermented sago in diets was 20%. Fermented sago can be applied up to 30% in diets, without decreasing the performance of body weight, dressed carcass weight, and dressed carcass percentage of Serati duck 8 weeks age